การพิมพ์ระบบดิจิตอลบนวัสดุสิ่งทอ (Digital Textile Printing) - ทองกุม อรสิริ (Science Essence Journal, 2012)
เทคโนโลยีระบบดิจิตอลได้ส่งเสริมคุณภาพชีวิตของมนุษย์มายาวนานมากกว่า 50 ปี และเครื่องพิมพ์ระบบดิจิตอลได้รับความนิยมอย่างแพร่หลายอย่างมากกับวัสดุสิ่งพิมพ์ประเภทกระดาษ แต่สำหรับการพิมพ์ระบบดิจิตอลบนวัสดุสิ่งทอพึ่งจะได้รับความสนใจเมื่อไม่นานมานี้ ประโยชน์ของการพิมพ์ระบบดิจิตอลบนวัสดุสิ่งทอที่เห็นเด่นชัด คือ การที่ทุกขั้นตอนตั้งแต่การออกแบบจนถึงการจัดจำหน่ายสามารถส่งข้อมูลผ่านระบบดิจิตอล เทคโนสารสนเทศ ซึ่งทำให้ผู้ผลิตสามารถตอบสนองความต้องการของลูกค้าได้อย่างรวดเร็ว และระบบการพิมพ์ดิจิตอลก็สามารถสร้างผลงานสร้างสรรที่เป็นเอกลักษณ์ โดยไม่มีข้อจำกัดทางด้านจำนวนสี และจำนวนสกรีนที่ต้องใช้เหมือนกับการพิมพ์แบบดั้งเดิม ดังนั้นการพิมพ์ระบบดิจิตอลบนวัสดุสิ่งทอจึงให้คุณภาพของงานพิมพ์ทั้งทางด้านความสวยงามและความคิดสร้างสรรค์ Digital Technology has enhanced human lives for over the past 50 years. The huge achieving digital printing on paper has been appeared for many years, but it is only during the past decade that the digital printing of textiles starts to become gradually popular. The main advantage of digital textile printing is based on the digital management system, where the manufacturing and distribution processes are implemented and controlled digitally. With the use of information technology, manufacturers can communicate with individual consumers through internet and customers’ printing demands are met immediately. Unlike conventional textile printing, digital printing cycle times are shorter and sample production can be done immediately. Furthermore, digital textile printing has led to new opportunities and created new markets, in which conventional textile printing methods are unable to accomplish. Digital textile printing can generate many new image-making possibilities without the limited numbers of colors or screen size of conventional printing. Digital textile printing also expands the concept of design aesthetics by its ability to yield more creative outcomes in textile printing industry.